Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis dan Kemampuan Berpikir Kreatif - Novrita Mulya Rosa; Anik Pujiati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
The purpose of the study was to determine the role of problem-based learning model to critical thinking ability and creative thinking ability. The subjects were students of semester IV Mathematics Education Study Program, University of Indraprasta PGRI, Jakarta in 2013/2014, in the subject of Basic Chemistry II. The selection of the class for this study was based on multistage random sampling. Experiments conducted on the sample of 30 experimental class students with problem-based learning model and 30 control class students with expository learning model. The data was collected by implementing tests of critical thinking ability and creative thinking ability with essay test. Analysis of research data using MANOVA support by SPSS. From the results of the study concluded that learning models give influence to the critical thinking ability and creative thinking ability together (F=21,815;p=0.000).